Spontaneous remission of primary hyperparathyroidism in a patient with neurofibromatosis type 1: case report - França, Mariana Martins; Santos, Antonio B. [UNESP]; Hirosawa, Renata Midori [UNESP]; Tagliarini, José Vicente [UNESP]; Mazeto, Gláucia Maria Ferreira da Silva [UNESP]; Nunes, Vania dos Santos [UNESP] (OMICS International, 2012)
Neurofibromatosis type 1 (NF1) is an autosomal dominant multisystem disorder affecting approximately 1 in 3500 individuals. Patients with the disorder can develop carcinoid tumors, medullary thyroid carcinoma, pheochromocytoma and tumor of the hypothalamus. The association of NF1 with Primary Hyperparathyroidism (HPP) is very rare. We report a 56-year-old woman with NF1 who was referred to our service because of nephrolithiasis. Physical examination revealed the characteristic signs of NF1, and her laboratory calcium profile was compatible with HPP. The patient was referred for parathyroidectomy, but during the surgical work-up she underwent spontaneous remission of her HPP. This case is significant not only for the rarity of this presentation in NF1 patients, but also because of the spontaneous remission of HPP.
Keywords: Neurofibromatosis type 1; Primary hyperparathyroidism; Autosomal dominant disease